Alafrasca sticta, a new genus and species of the tribe Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) with a checklist of the tribe from China - Lu, Si-Han; Qin, Dao-Zheng (Zootaxa, 2014)
A new monotypic genus of empoascine leafhopper, Alafrasca gen. nov. is described and illustrated for A. sticta sp. nov. from Sichuan, China as its type species. Habitus photos and illustrations of male genitalia of the new species are given. A checklist of the tribe in China is also provided.